Enhancement of joint properties and reduction of intermetallics in FSW of highly dissimilar Al/Ti alloys - Mustafa, Saed Enam; Rai, Rajiv Nandan; Firoz, Raashid (Welding in the world, 2023)
In this research work, welding of highly dissimilar aluminum alloy (6061-T6) and titanium alloy (Ti6Al4V) has been carried out using copper (Cu) interlayer with the friction stir welding (FSW) process by varying the tool rotation speed and tool traverse speed. FSW is a welding technique in which the plates to be joined are plastically deformed due to friction by a non-expendable rotating tool and welded as the tool traverses along the length of the plates. In the absence of any interlayer, the welded joint of the alloys, as mentioned above, failed along the joining surface due to the formation of the intermetallics, leading to low strength and brittleness. High strength and good quality joints are obtained using a Cu interlayer between the two alloys and a tapered tool at a lower tool rotation speed, and traverse speed due to appropriate deformation, uniform mixing, and effective temperature rise during welding. Also, using the interlayer between the Al and Ti alloys enhanced the joint strength by reducing the formation of Al 3 Ti intermetallic. Other non-optimal conditions resulted in wormhole defects and intermetallics formation, thus resulting in degraded joint quality and strength. The joint welded at optimum welding conditions failed in a pure ductile manner, while the others were either in hybrid or brittle mode. Tool rotation and traverse speeds are found to be crucial for proper mechanical mixing as they impact the weld’s structure, phase development, and mechanical characteristics. Furthermore, the optimal process parameters were validated with the help of ANOVA.